Strategi Pengembangan Objek Wisata Ngopi Bareng Pintu Langit di Desa Ledug Kecamatan Prigen Kabupaten Pasuruan - Muhammad Nawawi Syahfuddin; Ananta Prathama (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Tourism has an impact on the economic, social and cultural sectors. In the economic sector, tourism activities will increase state income. The purpose of this research is to find out how to describe and analyze the Strategy for Development of a Drinking Coffee with Pintu Langit Tourism Object in Ledug Village, Prigen District, Pasuruan Regency. The type of research used in this research is descriptive qualitative. This study uses primary data from key informants and secondary data from supporting documents. Data collection techniques used in this study were interviews with informants, direct observation in the field, and documentation. Then the data analysis model used in this study is using an interactive data analysis model, namely data collection, data presentation, data condensation, and drawing conclusions and verification. The results of this study found that: a) To focus on tourist attraction, the strategy used is to utilize the potential of Bendil Hill and create unique and interesting photo spots; b) In the focus of tourist attractions, the strategy used is to hold big events such as grand recitations and hold music concert attractions with famous musicians on a national scale; c) On the focus of tourist facilities and public facilities, the strategy used is the addition of sky gate transportation and kids zone as well as the addition of a large parking area, clean and sufficient toilets, and a large and clean prayer room that is always repaired; and d) On the focus of the accessibility of the strategy, namely the detection of tourism on google maps and publication of the social media owned by the tour.